New class of frequency-hopping sequences set with optimal average Hamming correlation property - Pin-hui KE; Hai-hui ZHANG; Sheng-yuan ZHANG (Tongxin xuebao)
The average Hamming correlation is an important performance parameter of frequency-hopping sequences.A generalization of Whiteman cyclotomy was proposed and then some properties of the new defined cyclotomy classes were presented.Based on the generalization of Whiteman cyclotomy,new classes of frequency-hopping sequences set were constructed.The proposed frequency-hopping sequences set was shown to be optimal with respect to the average Hamming correlation bound.